Functional Characterization of a Novel Heterozygous Mutation in the Glucokinase Gene That Causes MODY2 in Chinese Pedigrees - Jiang, Feng; Yan, Jing; Zhang, Rong; Ma, Xiaojing; Bao, Yuqian; Gu, Yujuan; Hu, Cheng (Frontiers in Endocrinology, 2021)
Background: Glucokinase (GCK) plays a central role in glucose regulation. The heterozygous mutations of GCK can cause a monogenic form of diabetes, maturity-onset diabetes of the young (MODY) directly. In our study, we aimed to explore the mechanism of the novel mutation GCK p.Ala259Thr leading to glucokinase deficiency and hyperglycemia. Methods: Thirty early-onset diabetes pedigrees were referred to whole exome sequencing for novel mutations identification. Purified wild-type and mutant GCK proteins were obtained from E.coli systems and then subjected to the kinetic and thermal stability analysis to test the effects on GCK activity. Results: One novel missense mutation GCK p.Ala259Thr was identified and co-segregated with diabetes in a Chinese MODY2 pedigree. The kinetic analysis showed that this mutation result in a decreased affinity and catalytic capability for glucose. The thermal stability analysis also indicated that the mutant protein presented dramatically decreased activity at the same temperature. Conclusion: Our study firstly identified a novel MODY2 mutation p.Ala259Thr in Chinese diabetes pedigrees. The kinetic and thermal stability analysis confirmed that this mutation caused hyperglycemia through severely damaging the enzyme activities and protein stability.